A Stable Dimer of SiS2 Arranged between Two Carbene Molecules. Issue 36 (15th July 2015) - Mohapatra, Chandrajeet; Mondal, Kartik Chandra; Samuel, Prinson P.; Keil, Helena; Niepötter, Benedikt; Herbst‐Irmer, Regine; Stalke, Dietmar; Dutta, Sayan; Koley, Debasis; Roesky, Herbert W.
Abstract The Me‐cAAC:‐stabilized dimer of silicon disulfide (SiS2) has been isolated in the molecular form as (Me‐cAAC:)2Si2S4 (2) at room temperature [Me‐cAAC:=cyclic alkyl(amino) carbene]. Compound 2 has been synthesized from the reaction of (Me‐cAAC:)2Si2 with elemental sulfur in a 1:4 molar ratio under oxidative addition. This is the smallest molecular unit of silicon disulfide characterized by X‐ray crystallography, electron ionization mass spectrometry, and NMR spectroscopy. Structures with three sulfur atoms arranged around a silicon atom are known; however, 2 is the first structurally characterized silicon–sulfur compound containing one terminal and two bridging sulfur atoms at each silicon atom. Compound 2 shows no decomposition after storing for three months in an inert atmosphere at ambient temperature. The bonding of 2 has been further studied by theoretical calculations.